Manajemen Kinerja di Institusi Pendidikan Tinggi: Kepuasan Kerja dan Budaya Organisasi - Hidayah, Siti Nur (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2016)
Individual performance in the organization is influenced by many factors, such as work satisfaction and culture within the organization. Besides that, work satisfactionhave a positif correlation with individual performance. The more satisfy a worker withhis/her work, the bettter his/her individual performance that make them to be moreproductive. Organizational culture influence which strategy that will be implementedby an organization to respond to the changes within or outside the organization. Themore capability of an organization to respond to changes, the better the organizationitself.